Strategi peningkatan kinerja karyawan Bank Negara Indonesia Kantor Cabang Pembantu Makale - Palamba, Wenef Natalia; Ma'na, Petrus; Pasae, Yoel; Tandi, Asrin (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
This study aims to analyze employee performance improvement strategies at Bank Negara Indonesia Makale Branch Office. Data were obtained from primary and secondary data through observation, interviews, and documentation. The research method used was qualitative using SWOT analysis. The results showed that the strength of employee performance lies in fulfilling the workload according to SOP and job description, a harmonious work environment, and adequate work facilities. However, there are several weaknesses such as delays in repairing work equipment, lack of human resources in customer service positions, and employees who are not domiciled in Makale. Opportunities in improving performance include employee motivation and career development, while threats include employees who are not domiciled in Makale and a lack of security personnel. Obstacles faced by employees include damaged work equipment, lack of human resources, and limited security personnel. Factors that support employee performance include fulfilling the workload, a harmonious work atmosphere, adequate work facilities, and employee motivation. It can be concluded that performance strengths must be maximized and must take advantage of opportunities so that performance continues to improve.